Isolated Pancreatic Metastasis from Locally Advanced Gastric Carcinoma: A Case Report - Ahmed, Akhter; Sarker, Rajib Dey; Salehin, Sadique; Islam, Md Jayedul; Khan, Nafiz Ahmed; Khan, Sereen Afza; Borshon, Asif Ahmed; Costa, Mishel (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Though rare, pancreas may occasionally serve as a favoured target from metastasis. Metastatic lesion of pancreas have been described for groups of primary origins, including gastric malignancy. Even after neoadjuvants, the surgery still remains a bonafide challenge. Case Presentation: We report a 54-year-old male with epigastric pain, anorexia and trifle weight lossin one month. Whipple’s with partial gastrectomy was advocated for gastric adenocarcinoma with pancreatic metastasis. Histopathology reports depicted metastasis to pancreatic head and in regional lymph nodes. Conclusion: Gastric malignancies may metastasize to unusual sites and even neoadjuvants may be inadequate to aid surgeon in his job. Radical resection gives better prognosis in addition to early diagnosis. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 161-163